Functional state of fetoplacental complex in pregnant women after abdominal delivery - A.Yu. Scherbakov; T.A. Gladkova; V.Yu. Scherbakov; H.A. Novikova (Zaporozhye State Medical University, 2012)
The results of research of indices of hormonal status in pregnant women after abdominal delivery are presented. Expedience of their determination with the purpose of diagnostics of placenta dysfunction which is one of reasons of prenatal morbidity and death rate is well-proven.